A new species of Bulbophyllum from Northern of Vietnam - Nguyen, van Tu; Averyanov, Leonid V.; Dang, van Son; Maisak, Tatiana V.; Bui, van Huong; Dang, Minh Quan; Boo, Sung Min; Truong, Ba Vuong (Phytotaxa, 2022)
A species, new to science, is described from Son La province, Vietnam. The new species is similar to B. yongtaiense, B. layae and B. sridithii in the hairy lip at base but clearly differs by the papillose margin and inner surface of dorsal sepal and petals, lip without mid keel and dense hairs on lateral keels, stelidia 2 times longer than 3 similar species.